The effect of connexin40 deficiency on ventricular conduction system function during development - Sankova, Barbora; Benes, Jiri; Krejci, Eliska; Dupays, Laurent; Theveniau-Ruissy, Magali; Miquerol, Lucile; Sedmera, David (Cardiovascular research, 2012)
AIMS: The aim of this study was to characterize ventricular activation patterns in normal and connexin40-deficient mice in order to dissect the role of connexin40 in developing the conduction system. METHODS AND RESULTS: We performed optical mapping of epicardial activation between ED9.5-18.5 and analysed ventricular activation patterns and times of left ventricular activation. Mouse embryos deficient for connexin40 were compared with normal and heterozygous littermates. Morphology of the primary interventricular ring (PIR) was delineated with the help of T3-LacZ transgene. Four major types of ventricular activation patterns characterized by primary breakthrough in different parts of the heart were detected during development: PIR, left ventricular apex, right ventricular apex, and dual right and left ventricular apices. Activation through PIR was frequently present at the early stages until ED12.5. From ED14.5, the majority of hearts showed dual left and right apical breakthrough, suggesting functionality of both bundle branches. Connexin40-deficient embryos showed initially a delay in left bundle branch function, but the right bundle branch block, previously described in the adults, was not detected in ED14.5 embryos and appeared only gradually with 80% penetrance at ED18.5. CONCLUSION: The switch of function from the early PIR conduction pathway to the mature apex to base activation is dependent upon upregulation of connexin40 expression in the ventricular trabeculae. The early function of right bundle branch does not depend on connexin40. Quantitative analysis of normal mouse embryonic ventricular conduction patterns will be useful for interpretation of effects of mutations affecting the function of the cardiac conduction system.
Keywords: Mice, Transgenic; Heart Conduction System; Penetrance; Connexins; gestační stáří; akční potenciály; myši transgenní; penetrance; převodní systém srdeční; zvířata; Action Potentials; myši; Mice; konexiny; myši knockoutované; Morphogenesis; Gene Expression Regulation, Developmental; lac operon; morfogeneze; Lac Operon; Mice, Knockout; blokáda Tawarova raménka; Bundle of His; Heart Ventricles; Gap Junction alpha-5 Protein; vývojová regulace genové exprese; Animals; Bundle-Branch Block; protein alfa 5 mezerového spoje; Voltage-Sensitive Dye Imaging; zobrazování pomocí barviva citlivého na potenciál; srdeční komory; Gestational Age; Hisův svazek